2016
DOI: 10.1175/jcli-d-15-0556.1
|View full text |Cite
|
Sign up to set email alerts
|

ERA-20C: An Atmospheric Reanalysis of the Twentieth Century

Abstract: The ECMWF twentieth century reanalysis (ERA-20C; 1900–2010) assimilates surface pressure and marine wind observations. The reanalysis is single-member, and the background errors are spatiotemporally varying, derived from an ensemble. The atmospheric general circulation model uses the same configuration as the control member of the ERA-20CM ensemble, forced by observationally based analyses of sea surface temperature, sea ice cover, atmospheric composition changes, and solar forcing. The resulting climate trend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
977
3
11

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 986 publications
(1,010 citation statements)
references
References 26 publications
19
977
3
11
Order By: Relevance
“…The 2 m T a in NCEP-1, NCEP-2, MERRA, MERRA-2, ERA-20C, ERA-20CM, CERA-20C, NOAA 20CRv2c, NOAA 20CRv2 and CFSR are model-derived fields that are functions of the surface skin temperature, the temperature at the lowest model level, the vertical stability and the surface roughness, which are constrained primarily by observations of upper-air variables and the surface pressure (Kanamitsu et al, 2002;Rienecker et al, 2011;Reichle et al, 2017;Poli et al, 2016;Hersbach et al, 2015;Laloyaux et al, 2016;Compo et al, 2011;Saha et al, 2010). However, the T a in ERA-Interim and JRA-55 are post-processing products by a relatively simple analysis scheme between the lowest model level and the surface and are analysed using ground-based observations of T a , with the help of Monin-Obukhov similarity profiles consistent with the model's parameterization of the surface layer (Dee et al, 2011b;Kobayashi et al, 2015).…”
Section: Reanalysis Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2 m T a in NCEP-1, NCEP-2, MERRA, MERRA-2, ERA-20C, ERA-20CM, CERA-20C, NOAA 20CRv2c, NOAA 20CRv2 and CFSR are model-derived fields that are functions of the surface skin temperature, the temperature at the lowest model level, the vertical stability and the surface roughness, which are constrained primarily by observations of upper-air variables and the surface pressure (Kanamitsu et al, 2002;Rienecker et al, 2011;Reichle et al, 2017;Poli et al, 2016;Hersbach et al, 2015;Laloyaux et al, 2016;Compo et al, 2011;Saha et al, 2010). However, the T a in ERA-Interim and JRA-55 are post-processing products by a relatively simple analysis scheme between the lowest model level and the surface and are analysed using ground-based observations of T a , with the help of Monin-Obukhov similarity profiles consistent with the model's parameterization of the surface layer (Dee et al, 2011b;Kobayashi et al, 2015).…”
Section: Reanalysis Productsmentioning
confidence: 99%
“…The climate reanalyses of this new generation extend back to the late nineteenth century and include the Climate Forecast System Reanalysis (CFSR), which is produced by the National Centers for Environmental Prediction (Saha et al, 2010); NOAA 20CRv2c, which is produced by the University of Colorado's Cooperative Institute for Research in Environmental Sciences (CIRES) in cooperation with the National Oceanic and Atmospheric Agency (NOAA) (Compo et al, 2011); and ERA-20C (Poli et al, 2016), ERA-20CM (Hersbach et al, 2015) and CERA-20C , which are produced by the ECMWF. Compo et al (2013) suggested that the NOAA 20CRv2c reanalysis can reproduce the trend in global mean surface air temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, a period in which the multi-proxy reconstructions overlap with the instrumental DJF SOI (1876-1977) was assessed. Analysis using longer twentieth century reanalysis for a logbook-type reconstruction over this period is not carried out due to additional sources of uncertainty when using twentieth century reanalyses which span further back in time and are informed from a smaller number of observations (Ferguson and Villarini 2014;Poli et al 2016;Bett et al 2017). The documentary chronologies have a more limited period of overlap with the instrumental SOI, with ORT00 and GH08 only providing an ENSO chronology up to 1900.…”
Section: Methodsmentioning
confidence: 99%
“…Rather, by tendency most of the reanalysis data sets [except for ERA-20C described in Poli et al (2016), CERA-20C described in Laloyaux et al (2016) and 20-CR introduced in Compo et al (2011), which try to achieve climate quality] offer the best analysis quality at any point of time.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, this appraisal has put forward the idea of regional reanalyses additionally to the global ones [for global reanalyses see e.g. Kalnay et al, (1996); Onogi et al (2007); Saha et al (2010); Rienecker et al (2011); Dee et al (2011);Compo et al (2011); Kobayashi et al (2015); Poli et al (2016)]. Regional reanalyses make use of limited-area models with high grid resolution and thus 'zoom in' to a certain geographical region.…”
Section: Introductionmentioning
confidence: 99%